Migrants and religion paths, issues, and lenses : a multidisciplinary and multi-sited study on the role of religious belongings in migratory and integration processes - Zanfrini, Laura ca. 21. Jh. (Leiden Boston Brill, 2020)
Despite the worldwide dramatic spread of religious-based discriminations, persecutions, and conflicts, both official data and academic literature have underestimated their role as a root cause of contemporary migrations. This multidisciplinary study aims to overcome this gap. Through an unprecedented collection of theoretical analysis and original empirical evidence, the book provides unique data and insights on the role of religion in the trajectories of asylum seekers and migrants - from the analysis of the religious geography of sending countries to the role of spirituality as a factor of resilience and adaptation. By enhancing both academic and political debate on these issues, the book offers the possibility of regaining awareness of the close link between religious freedom and the quality of democracy.
Religious education in schools as a necessity in a secular state : the perspective in Catalonia Núria Llevot-Calvet, Olga Bernad-Cavero and Jordi Garreta-Bochaca
Literaturangaben, Register
Keywords: Emigration and immigration -- Religious aspects -- Case studies; Religious refugees -- Social conditions -- Case studies; Immigrants -- Religious life -- Case studies; Freedom Of Religion; Belonging (Social psychology)